La gestion culturelle des musées au prisme du développement durable : évolution et enjeux contemporains - Porcedda, Aude (Muséologies, 2021)
Since the 2000s, the museal sector has had to face the combined challenges of sustainabilty, a fresh range of management tools coming from “new management,” and the digital revolution. While there was no real organizational disruption, several strategic behavioral patterns were observed. In fact, this changing environment brought about a progressive implementation of new tools and practises within cultural organizations. It seems important today to reevalute these organizations’ management strategies, particularly in the context of increasing globalization. First of all, there must be an awareness of research in this field to allow for the proposal of a theoretical framework that can provide the elements of comprehension of the functioning of today’s museal organizations. Analysis of the three examples of integrating a policy of sustainable development will then lead to a concrete illustration of the challenges to be met in order to conclude which contemporary issues museal management must meet today and in the future.